2009
DOI: 10.1002/rcm.4138
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic interaction chromatography/tandem mass spectrometry for the simultaneous determination of three polar non‐structurally related compounds, imipenem, cilastatin and an investigational β‐lactamase inhibitor, MK‐4698, in biological matrices

Abstract: A method coupling hydrophilic interaction chromatography (HILIC) with tandem mass spectrometry (MS/MS) has been developed for the simultaneous determination of three polar non-structurally related compounds--a carbapenem antibiotic, imipenem (IMP), a renal dehydropeptidase inhibitor, cilastatin (CIL), and an investigational beta-lactamase inhibitor, MK-4698 (BLI), in rat plasma, monkey plasma and mouse blood. The analytes were extracted through protein precipitation, chromatographed on a Waters Atlantis HILIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A large diversity of pharmaceutical compounds, belonging to different therapeutical classes, has been analyzed in HILIC mode using bare‐silica as SP 21–52. Both non‐biological 27, 31, 35, 36, 38, 41, 44, 51 and biological 21–26, 28–30, 32–34, 37, 39, 40, 42, 43, 45–50, 52 assays are described. The finally reported experimental conditions are presented in Table 1.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…A large diversity of pharmaceutical compounds, belonging to different therapeutical classes, has been analyzed in HILIC mode using bare‐silica as SP 21–52. Both non‐biological 27, 31, 35, 36, 38, 41, 44, 51 and biological 21–26, 28–30, 32–34, 37, 39, 40, 42, 43, 45–50, 52 assays are described. The finally reported experimental conditions are presented in Table 1.…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…Imipenem (2 g daily, 0.5 hour infusion of 0.5 g every 6 to 8 hours) provides sufficient drug exposure in the pediatric burn patients investigated in the present study according to data reported previously in critically ill adult patients (Dailly et al, 2003;Xu et al, 2009).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 52%
“…Several drug measurements have been reported previously for imipenem in biological matrices by applying microbiological techniques (Pietroski et al, 1991) and chromatographic methods such as LC-UV (Buckley et al, 1992;Belzeberg et al, 2004;Ebey, Boucher, Pieper, 1988;Garcia-Capdevila et al, 1997;Gravallese et al, 1984;Kurihara, Kizu, Hori, 2008;Legrand et al, 2008;) and LC-MS/MS (Xu et al, 2009). With regard to the drug assay for imipenem dose adjustment, LC-UV was preferred by its relative low cost relative to routine LC/MS/MS drug plasma measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used for retaining very polar organic molecules that may not be retained by RP columns [8]. Unlike the highly aqueous mobile phases required for polar molecule retention in RP separations, HILIC conditions employ high percentages of organic solvent in the mobile phase, which is ideal for optimizing mass spectrometric sensitivity [9].…”
Section: Chromatographymentioning
confidence: 99%